PROFIL DAN POLA LITERASI REMAJA DALAM PEMANFAATAN MEDIA SOSIAL: KAJIAN PADA SISWA SMA NEGERI 1 MERAWANG KABUPATEN BANGKA - Aegustinawati Aegustinawati; Soemedi Hadiyanto (JURNAL PENDIDIKAN ROKANIA, 2021)
Adolescents in storm and stress conditions need to actively optimize their social media literacy, especially to optimize the learning process. The research aims to describe the socio-economic background related to literacy patterns and maps in the use of social media for adolescents at SMA Negeri 1 Merawang. Descriptive quantitative research method with a sample of 332 students from 414 students (80.19%), conducted March 1-5, 2021, using the googleforms feature and distributed via WhatsApp. The measuring instrument is a structured list of questions, processed using the SPSS for Windows program. The results show that the parents' income is below the provincial minimum wage but can still access social media using a data network that is purchased every month. Adolescents use social media as a medium to sell online. The use of social media is dominated by WhatsApp (94.67%), Instagram (60.87%) and Facebook (20.81%). Adolescent social media literacy is passive and not yet productive, namely writing and creating creative video content. Improving the quality of learning is by optimizing communication through social media and creating innovative and creative learning events